2016
DOI: 10.3889/oamjms.2016.036
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Body Adiposity Indices in Predicting Metabolic Syndrome and Its Components among Egyptian Women

Abstract: AIM:To assess the associations between the body adiposity indices and risk of metabolic syndrome (MS) and its components in Egyptian women and to evaluate their predictive power.MATERIALS AND METHODS:This was a cross-sectional analysis performed on 180 Egyptian women aged between 25-35 years. They were 90 women with MS diagnosed by International Diabetes Federation (IDF) and 90 healthy age matched controls. Body adiposity index (BAI), body mass index (BMI), waist to hip ratio (WHR) and waist to height ratio (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…Although recent studies [ 9 , 31 , 32 , 33 ] have suggested that BAI-BF% can provide an estimate of BF% without the need for further adjustment, our results indicate that these estimates will be systematically biased by gender, level of adiposity, and diet. Additionally, BAI-BF% is claimed to have several advantages over BMI, in that it yields similar associations with BF% for men and women and may be more practical to assess in field studies, because it does not require weight measurement and can be used to reflect BF% in adults [ 15 ].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Although recent studies [ 9 , 31 , 32 , 33 ] have suggested that BAI-BF% can provide an estimate of BF% without the need for further adjustment, our results indicate that these estimates will be systematically biased by gender, level of adiposity, and diet. Additionally, BAI-BF% is claimed to have several advantages over BMI, in that it yields similar associations with BF% for men and women and may be more practical to assess in field studies, because it does not require weight measurement and can be used to reflect BF% in adults [ 15 ].…”
Section: Discussioncontrasting
confidence: 78%
“…Additionally, BAI-BF% is claimed to have several advantages over BMI, in that it yields similar associations with BF% for men and women and may be more practical to assess in field studies, because it does not require weight measurement and can be used to reflect BF% in adults [ 15 ]. In this line, Zaki et al [ 31 ] suggested that BAI-BF% could be used to mirror BF% for adult men and women of differing ethnicities without numerical correction. However, as observed by Freedman et al [ 32 ], analyses of body fat that do not control for sex should be interpreted very cautiously; due to the fact that women are generally shorter than men and have more body fat, an analysis of the association between height and body fat might greatly overstate the strength of the association.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we observed that BMI, WC, and TG to steadily increased across the SUA quartiles, and secondly, we observed a significant inverse association with HDL-C. Our study findings are in line with previous studies that showed a positive association between SUA and adiposity such as overweight and obesity. Zaki et al 28 in a cross-sectional study among Egyptian women also reported that BMI and waist-tohip ratio to be correlated with metabolic syndrome. Among studies conducted in Asia, BMI 29 and central obesity 30 have been associated…”
Section: Discussionmentioning
confidence: 91%
“…Our study findings are in line with previous studies that showed a positive association between SUA and adiposity such as overweight and obesity. Zaki et al 28 in a cross‐sectional study among Egyptian women also reported that BMI and waist‐to‐hip ratio to be correlated with metabolic syndrome. Among studies conducted in Asia, BMI 29 and central obesity 30 have been associated with SUA among adults.…”
Section: Discussionmentioning
confidence: 92%
“…However, among the variables used to determine the visceral adiposity index, there are MS diagnosis criteria. Therefore, a correlation between them could exist [ 27 , 31 ], and they should not be used to diagnose SM. Likewise, other authors have used VAI and LAP to establish the presence of T2DM and prediabetes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%